Cultural adaptation and validation of Patient and Observer Scar Assessment Scale for Turkish use - YURDALAN, SAADET UFUK (ELSEVIER SCI LTD, 2018)
Background: This study aimed to evaluate cross-cultural adaptation, validation, and reliability of Patient and Observer Scar Assessment Scale (POSAS) for its Turkish use. Method: This study included 50 burn patients with hypertrophic scars who were aged 18-65 years (mean, 37.5 +/- 1.4years) and were admitted to Wound and Burn Treatment Center from February 2014 to April 2014. With regard to the cultural adaptation of POSAS from English to Turkish, the scale was translated by two people who worked in different health fields. POSAS was administered to the patients with a 1-week interval to evaluate the validity and reliability of the scale. Internal consistency of the scale was tested using the Cronbach alphamethod. Results: The Cronbach alpha value for the observer measurements was found to be 0.93 (excellent), and that for patient measurements was found to be 0.77 (good). Accordingly, the internal consistency of the scale was established. Conclusion: The Turkish version of POSAS is a valid, reliable and culturally appropriate survey for evaluating hypertrophic scars. We believe that the Turkish version of POSAS will be an important clinical/scientific tool in the field of burn physiotherapy in Turkey, which will lead to new researches in this field. (C) 2018 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Patient and Observer Scar Assessment Scale; Hypertrophic scar; Physiotherapy; Validity; Reliability; RELIABILITY; POSAS